Demonstration of the role of cytophilic antibody in resistance to malaria parasites (Plasmodium berghei) in rats. - Green, T J (1978)
This paper reports the results of a study of the nature of the immune response against Plasmodium berghei parasites by inbred rats. A macrophage-cytophilic antibody specific for malarial antigens was identified and characterized. Detection of the antibody on the macrophage surface was accomplished by the parasite adherence tests and by the indirect fluorescent antibody technique. Isolation and purification of the macrophage-cytophilic and opsonic antibodies from hyperimmune rat serum was accomplished by QAE-Sephadez A-50 elution chromatography, and of the macrophage-cytophilic antibody by adsorption with and elution from syngeneic macrophages as well. Characterization of the cytophilic antibody as immunoglobulin G1 was done by immunoelectrophoresis and by Ouchterlony-type double diffusion in gel. Passive protection tests in weanling inbred rats have demonstrated that the opsonizing antibody conferred some protection against P. berghei. The macrophage-cytophilic antibody, on the other hand, was not protective alone but acted synergistically with the opsonizing antibody.